Improving English Reading Skills of 8th Grade Students at Muhammadiyah 2 Boarding School Using Discovery Learning Method through Role Play Strategy: Classroom Action Research - Lestari, Endang; Rahmi, Nur (ITScience (Information Technology and Science), 2024)
This study investigates the effectiveness of the Discovery Learning method combined with Role Play strategy in improving the English reading skills of 8th-grade students at Muhammadiyah 2 Boarding School. The research addresses the challenges students face in reading comprehension, which is crucial for their academic success. The study employs a classroom action research. There are 22 students as the sampling. Data was collected through two cycles namely cycle I and cycle II, along with descriptive quantitative and student feedback. Result indicates a significant improvement in reading skills among students. In pre-cycle the students average score was about 70,54(55%). It is indicated that they don’t pass the passing grade. Through cycle I, the score was increased to 75,55 or there were 8 (36%) students who didn’t pass the passing grade. Moreover in cycle II, the student average score was increase to 8,04 point (83,59). There were 2 students (9%) who didn’t pass the passing grade. The Discovery Learning method, which encourages students to explore, inquire, and engage actively with the material, fosters deeper understanding and retention. The Role Play strategy enhances this by allowing students to immerse themselves in various contexts, making the reading experience more relatable and enjoyable. This approach not only improves reading comprehension but also boosts students’ motivation and engagement in learning. The findings suggest that incorporating interactive and student-centered methods, such as Discovery Learning and Role Play, can lead to enhanced language skills and better educational outcomes and underscores the importance of innovative teaching strategies in fostering effective learning in English class.